Diferencias oviposicionales entre hembras de Boophilus microplus, Canestrini (Acari: Ixodidae) de diferente peso en Heredia, Costa Rica - Herrero, Marco V. (1988)
A caged study was conducted to compare preoviposition, oviposition, posoviposition and maximum free living periods among Boophilus microplus (Canestrini) females of three different weight categories. Significant differences (p<0.01) on the oviposition period were found among the three groups.  No significant differences were found among other periods.